Modals and conditionals - Kratzer, Angelika (Oxford studies in theoretical linguistics, 2012)
This book contains updated and substantially revised versions of Angelika Kratzer's classic papers on modals and conditionals, including 'What 'must' and 'can' must and can mean, ' 'Partition and Revision, ' 'The Notional Category of Modality, ' 'Conditionals, ' 'An Investigation of the Lumps of Thought, ' and 'Facts: Particulars or Information Units?' The book's contents add up to some of the most important work on modals and conditionals in particular and on the semantics-syntax interface more generally. It will be of central interest to linguists and philosophers of language of all theoretical persuasions.